2009
DOI: 10.4067/s0716-10182009000600003
|View full text |Cite
|
Sign up to set email alerts
|

Evolución del consumo de antibióticos y de la susceptibilidad antimicrobiana en el Centro Hospitalario Pereira Rossell en la era de Staphylococcus aureus resistente a meticilina

Abstract: Antibiotic consumption and antimicrobial susceptibility evolution in the Centro Hospitalario Pereira Rossell in methicillin resistant Staphylococcus aureus era Introduction: In the past few years, an increase in methicillin resistant-not multiresistant Staphylococcus aureus was observed in Uruguay among children with community acquired infections. Recommendations for empiric antibiotic treatment required adjustments and new national guidelines were recommended in July 2004. Adherence to these guidelines was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…Estudios microbiológicos señalan que la gravedad de S. aureus no es una característica exclusiva de las cepas resistentes a meticilina, si bien éstas parecen poseer más atributos de virulencia, como la producción de una proteína de unión al colágeno (CNA) y de una exotoxina la leucocidina de PantonValantine que destruye los neutrófilos del hospedero generando inmunocompromiso y aumentando el riesgo de coagulopatía intravascular. Conduce además a la producción de material purulento más aglutinado, difícil de drenar y erradicar, por lo que el abordaje quirúrgico generalmente es más complejo y frecuente [36][37][38][39] . Las dos muertes se registraron también en este grupo etiológico.…”
Section: Discussionunclassified
“…Estudios microbiológicos señalan que la gravedad de S. aureus no es una característica exclusiva de las cepas resistentes a meticilina, si bien éstas parecen poseer más atributos de virulencia, como la producción de una proteína de unión al colágeno (CNA) y de una exotoxina la leucocidina de PantonValantine que destruye los neutrófilos del hospedero generando inmunocompromiso y aumentando el riesgo de coagulopatía intravascular. Conduce además a la producción de material purulento más aglutinado, difícil de drenar y erradicar, por lo que el abordaje quirúrgico generalmente es más complejo y frecuente [36][37][38][39] . Las dos muertes se registraron también en este grupo etiológico.…”
Section: Discussionunclassified
“…Other authors have reported higher incidence of S. aureus in the nasal cavity of healthy children [14,25]. The highest prevalence was found in males, being this predominance also common in other research with children [26] and adults [27,28].…”
Section: Resultsmentioning
confidence: 48%
“…Because most reports suggest that the frequency of hVISA, although increasing, is low and related to the use of vancomycin, we proposed to analyze all MRSA strains isolated over an extended period in a reference pediatric hospital which serves children from all over the country and where the use of vancomycin has increased since 2002. In doing so, we may be able to increase the likelihood of recovering strains with DSG to glycopeptides [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Most hVISA strains described from Asia, South America and Europe are MRSA isolated from adults and belong to ST5, ST8 and ST239. There are no data about the prevalence and microbiological characteristics of hVISA in MRSA recovered from children in Uruguay [6][7][8]. The aim of this research was to detect decreased susceptibility to glycopeptides (DSG) in MRSA strains isolated from children with invasive diseases assisted at the local reference public hospital between 2009 and 2019.…”
Section: Introductionmentioning
confidence: 99%